Fenomena Bilingualisme (Campur-Alih Kode) Bahasa dalam Percakapan Santri di Pondok Pesantren Al Manshur Popongan Klaten - Nurul Yuwana Ning Tyas; Elen Inderasari; Wahyu Oktavia (Balai Bahasa Kalimantan Tengah, 2020)
This study aims to discuss one of the phenomena of bilingualism (code switching) and interference as well as the factors causing the phenomenon of language bilingualism in santri conversations in Islamic boarding schools. The forms of bilingualism and interference include Javanese, Indonesian and Arabic. The approach in this research is descriptive qualitative which describes the state of the object of research based on the facts that appear as they are. The subjects of this study were the students of Al Manshur Popongan Klaten. Data collection techniques in the form of observation, interviews and documentation. The analysis technique during the field uses the model of Miles and Huberman, namely data collection, data reduction, data presentation and conclusion or verification. The results of the study note that there are 55 conversational data in the Al Manshur Popongan Islamic boarding school classified as follows; internal code 7 data transfer, external code 10 data transfer. Mix codes in linguistic elements that occur namely mixed code insertion of 12 data tangible elements, mixed code 5 data tangible codes, mixed code insertion elements in clause 7 data and mixed code insertion elements in the 5 word repetition element. Factors causing code switching and code mixing are the presence of speakers, interlocutors, prestige, changes in topic of conversation, identification of social roles, the desire to explain, and the habit of speakers.AbstrakPenelitian ini bertujuan untuk membahas salah satu fenomena bilingualisme (campur-alih kode) bahasa serta faktor-faktor penyebab terjadinya fenomena bilingualisme bahasa dalam percakapan santri di Pondok Pesantren Al Manshur, Popongan, Klaten. Wujud bilingualisme meliputi bahasa Jawa, bahasa Indonesia, dan bahasa Arab. Pendekatan dalam penelitian ini adalah kualitatif yang memaparkan keadaan objek penelitian dengan berdasarkan fakta-fakta yang tampil apa adanya. Subjek dari penelitian ini adalah para santri Al Manshur, Popongan, Klaten. Teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi. Teknik analisis selama di lapangan menggunakan model Miles and Huberman, yaitu pengumpulan data, reduksi data, penyajian data, dan kesimpulan atau verifikasi. Hasil penelitian diketahui bahwa terdapat 50 data percakapan di Pondok Pesantren Al Manshur, Popongan, Klaten, yang diklasifikasikan menjadi alih kode internal 7 data, alih kode eksternal 11 data, campur kode penyisipan unsur berwujud kata 12 data, campur kode berwujud frasa 5 data, campur kode penyisipan unsur berwujud klausa 7 data, dan campur kode penyisipan unsur berwujud perulangan kata 8 data. Adapun faktor penyebab terjadinya alih kode dan campur kode ialah adanya penutur, lawan tutur, gengsi, perubahan topik pembicaraan, identifikasi peranan sosial, keinginan untuk menjelaskan, dan keterbiasaan penutur.